Fully flax-derived composites based on epoxidized linseed oil matrix and flax fibers. Advancing sustainable performance through fiber treatment - Dinu, Roxana; Lafont, Ugo; Damiano, Olivier; Mija, Alice (Industrial crops and products, 2025)
This work reports on the fabrication of composite materials entirely derived from flax, using epoxidized linseed oil (ELO) as a biobased epoxy matrix and flax fibers as natural reinforcement. The central objective is to demonstrate that targeted surface treatments of the fibers can markedly improve fiber-matrix compatibility, as well as the mechanical performance, thermal stability, and moisture resistance of the composites. Flax woven fabrics were subjected to a three-step environmentally friendly treatment designed to enhance interfacial adhesion and reduce their natural hydrophilicity. Comprehensive analyses, including Dynamic Mechanical Analysis (DMA), Thermogravimetric Analysis (TGA), Interlaminar Shear Strength (ILSS) testing, compressive strength testing, Scanning Electron Microscopy (SEM), and water uptake measurements, confirmed the improved mechanical, thermal, and moisture-resistance properties of the treated composites. The treated flax composites exhibited a glass transition temperature (Tg) of about 82 °C, compressive strength close to 69 MPa, interlaminar shear strength around 18 MPa, density of 1.1 g cm⁻³ , hardness of 87 Shore D, and a water absorption rate of only 2.5 % after 24 h (compared to 9.1 % for untreated fibers). These findings highlight the effectiveness of treated plant fibers in improving the performance of biobased composites and underscore their promise for industrial sectors requiring materials that combine good mechanical properties with lower environmental impact. Moreover, by offering a renewable alternative to fossil-derived composites, this approach contributes to global sustainability targets and paves the way for greener, more durable composite technologies. [Display omitted] •Fully flax-derived composites using ELO and treated flax fibers were developed.•Fiber treatment enhanced compressive strength up to 69 MPa.•Improved ILSS observed: from 6 MPa (untreated) to 18 MPa (treated).•Treated fibers reduced water absorption by over 65 %.•SEM confirmed stronger fiber-matrix bonding after fiber surface treatment.